일개 지역사회 중심 가정간호시범사업소의 성과평가 연구 - 김세영(Se Young Kim); 박성애(Sung Ae Park) (지역사회간호학회지, 2008)
Purpose: This study was aimed to evaluate the performance of a community-based home care services model. Method: The subjects were 138 patients who have been enrolled during a 6 month's period, nursing records and nursing service bills. The data was collected by self report and chart review. The mean cost per visit was compared with those of hospitalization & clinic visit in the data from National Health Insurance Corporation. Result: A significant number of patients were bed ridden(63.8%) and unconscious (27.5%), and most of the patients had complex chronic diseases. Except nursing assessment, bed sore care was the most frequent nursing treatment(25.1%) in home care services. The mean cost per visit of home care services was 34,665 won, which was lower than those of hospitalization & clinic visit for medical aid. The patients were highly satisfied with the services by visiting nurse specialists. Conclusion: Community-based home care services provided cost-effective and satisfied services. Community-based home care services needs systematic supports to expand it's domain for promoting community health.